2005
DOI: 10.33997/j.afs.2005.18.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Primary Production and Fish Yield Estimation in the Meghna River System, Bangladesh

Abstract: This study was carried out in four selected stations (Mohonpur, Kaligonj, Charludua and Daulatkhan) in the Meghna river system, Bangladesh between the latitude 22°35.494Ñ N - 23°23.987 N and longitude 90°35.793 E - 90°49.061Ñ E. Average net primary production (NPP) and gross primary production (GPP) (gC·m3 ·h) in the euphotic zone of the Meghna river were 0.089 ± 0.021 and 0.161 ± 0.025 respectively. The rate of conversion of GPP into NPP ranged between 48.17 and 62.63% with an average of 54.72%. The mean rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…The higher DO values indicate higher productivity and might play a significant role for the migration of hilsa". The result was like the findings reported by Ahmed et al [22] and "they recorded the mean value of DO as 6.7±0.81 mg/L in the Meghna River". Dissolved Oxygen in the study (Table 2) results the growth and reproduction of fishes in these rivers.…”
Section: Dissolved Oxygen (Do)supporting
confidence: 90%
See 4 more Smart Citations
“…The higher DO values indicate higher productivity and might play a significant role for the migration of hilsa". The result was like the findings reported by Ahmed et al [22] and "they recorded the mean value of DO as 6.7±0.81 mg/L in the Meghna River". Dissolved Oxygen in the study (Table 2) results the growth and reproduction of fishes in these rivers.…”
Section: Dissolved Oxygen (Do)supporting
confidence: 90%
“…The concentration of nitrate 0.02-1.0 ppm is lethal to many fish species [35, > 1.0 ppm is somewhat lethal for many warm water fishes and < 0.02 ppm is acceptable [53] whereas Santhosh and Singh [54] recommended that nitrite concentration in water should not exceed 0.5 mg/L. Similar findings were observed by Ahmed et al [22] who reported that "ammonia concentration was found to be elevated and ranged from 0.1 to 0.6 mg/L and showed a gradual decreasing trend from the upward to the downward stretches in the Meghna River systems". The nitrate concentration was found within the acceptable range.…”
Section: Water Nutrientssupporting
confidence: 53%
See 3 more Smart Citations